THE SUMMIT SILIWANGI HOTEL DI BANDUNG: TINJAUAN PADA PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2013)
The purpose of a business established is the company can grow and develop (Huseini, 2001: Organization Theory lecture material). 'Growing up' can mean a number of companies are increased. 'Growing up' can also mean although its branches remain 1 (one) but care facilities are given more. If the company grows and develops career opportunities for employees will be available. If the career opportunities available, the employee was, in turn, will also grow and evolve. Availability exciting career will give hope to the employees. Hope can bring the work excitement.Efforts to enable companies to grow and develop associated with the company's efforts to remain in the community recognized. In essence if the company stands in a region, then it must be able to provide benefits to the surrounding community. If people feel the benefits, the public will automatically support the company's presence in the region.One of the company's efforts to provide benefits to the surrounding community is by doing Corporate Social Responsibility (CSR). CSR’s target includes four main areas. There are environment, guests, employees, and shareholders